BREXIT and foreign direct investment: Key issues and new empirical findings - Paul J. J. Welfens; Fabian J. Baier (International Journal of Financial Studies, 2018)
This contribution takes a new look at the gravity equation model in relation to foreign direct investment (FDI) of leading industrialized countries which presents a useful basis for assessing certain potential impacts arising from BREXIT-the envisaged leaving of the EU by the United Kingdom. The gravity equation estimated subsequently allows one to consider the case of BREXIT and the broader role of EU membership and other variables. Looking at the period from 1985 to 2012 for a dataset which contains 34 OECD (Organisation for Economic Co-operation and Development) countries, Pseudo Poisson Maximum Likelihood (PPML) dyadic fixed estimations take into account a broad set of approaches and variables. Besides the traditional variables of the EU/EU single-market membership of the source country and of the host country, we further consider the role of trade openness as well as corporate tax rates and the ratio of inward FDI stock to total capital stock. The analysis shows that trade openness is a variable which can be largely replaced by the inward FDI stock/capital stock ratio so that gravity FDI modeling with a strong emphasis on trade openness is likely to overstate the role of trade and to understate the role of relative FDI accumulation effects. The implication for BREXIT analysis is that the UK will face three impulses for FDI inflows: (1) leaving the EU single market will strongly reduce FDI inflows; (2) if foreign ownership in UK capital stock should strongly increase in the run-up to the BREXIT year 2019, part of the dampening effects of leaving the EU will be mitigated by the increase of the FDI stock/capital stock ratio, which in turn is likely to reflect a Froot-Stein effect related to real pound depreciation for 2016-2018; (3) to the extent that the UK government will want to reinforce output growth through higher FDI inflows, a reduction of corporate taxation could generate high effects but could also stimulate a downward international corporate tax reduction game.
Keywords: C32; E65; F21; F23; O52; 330; foreign direct investment; BREXIT; gravity equation; corporate taxation; EU single market